Targeting Reactive Astrocytes with Flavonoids to Alleviate Neuroinflammation and Promote Synaptic Function - Devendra Pratap Rao; Ammar Kh. Hammad; Hussein Riyadh Abdul Kareem Al-Hetty; Ali K. Kareem; Ahmed Hjazi; Irfan Ahmad; Zahraa Abbas; Reham Yahya Albaz; Yasser Fakri Mustafa; Mashael Abdulmohsin Zuhair Abdulmoaty (Molecular Neurobiology, 2026)

Yucca schidigera Roezl ex ortgies (Mojave yucca): an updated review of its phytochemistry, ethnopharmacological, and pharmacological properties - Dina S. Ghallab; Reham Mustafa; Salma Ramadan Mostafa; Riham A. El-Shiekh; Nihal M. El Newehy (Natural Product Research, 2025)

Seaweed valorization as anaerobic co-substrate with fat, oil, and grease: Biomethane potential and microbial dynamics - Shah Faisal; Adel W. Almutairi; Irfan Saif; Li Ting; Qingyuan Wang; Ahmad Mustafa; Reham Ebaid (Bioresource Technology, 2025)

Cleaner and sustainable synthesis of high-quality monoglycerides by use of enzyme technologies: techno-economic and environmental study for monolaurin - Ahmad Mustafa; Sara Fathy; Ozben Kutlu; Fumiya Niikura; Abrar Inayat; Muhamad Mustafa; Tamer M. M. Abdellatief; Awais Bokhari; Olusegun David Samuel; Carlo Pastore; Luigi di Bitonto; M. A. Tawfik; et al. (Clean Technologies and Environmental Policy, 2023)
Currently, monoglycerides (MG) are produced using a complicated energy-intensive technology that contributes negatively toward greenhouse gas mitigation. This work suggests a cleaner and simpler one-step enzymatic production of α -monolaurin in an inert membrane reactor, where the reaction and enzyme separation are conducted simultaneously in one unit. Candida antarctica lipase (Lipozyme 435) was used to catalyze the esterification reaction between lauric acid and glycerin in a solvent-free system under mild temperatures. Response surface methodology was used to optimize the reaction conditions. The optimal conditions were a molecular sieve of 14.85% w/w, a temperature of 56.95 °C, an enzyme amount of 5.38% w/w, and a molar ratio of 4.75% w/w. The gas chromatography (GC) analysis showed that the α-monolaurin percentage was 49.5% when the enzymatic process (ENZ) was used. The conventional chemical (CHEM) and autocatalytic (AUT) esterification methods were also performed to study their proportional MG yields. The GC results showed the MG percentages of 43.9 and 41.7% for CHEM and AUT, respectively. Economic analysis was also conducted for the suggested enzymatic technique, and the findings were compared with those of the CHEM and AUT technologies. Using a plant capacity of 4950 t/year and 11% interest for the proposed ENZ process, the total capital investment of α-monolaurin production was preferably four times less than that of the CHEM process and three times less than that of the AUT method, presenting investment possibilities. However, the ENZ process showed the least profitability (net profit per day) among the three processes. Nevertheless, the return on investment and net present value for the ENZ process were preferably higher than those of CHEM and AUT because of its interestingly lower inside battery limit plant cost and less energy consumption. The AUT/CHEM processes generated a total carbon dioxide (CO 2 ) exhaust of 678.7 t CO 2 eq./year. In contrast, the ENZ process exhausted a total CO 2 of only 50 t CO 2 eq./year. The present integrated techno-economic and environmental study of α-monolaurin production emphasizes the green and cost benefits of the proposed ENZ technology. Graphical Abstract

Enhancement of phenolic content, antioxidant and cytotoxic activities of Moringa oleifera leaf and seed by suspension culture - Reham Mustafa; E. M. B El-Naggar; Emil Svajdlenka; Gamal Omran; Fathy ELFiky; Amr El-Hawiet (Natural Product Research, 2021)

Profiles of multidrug-resistant organisms among patients with bacteremia in intensive care units: an international ID-IRI survey - Rehab El-Sokkary; Serhat Uysal; Hakan Erdem; Ravina Kullar; Abdullah Umut Pekok; Fatma Amer; Svjetlana Grgić; Biljana Carevic; Amani El-Kholy; Anna Liskova; Mehmet Özdemir; Ejaz Ahmed Khan; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)